Electronic and photovoltaic properties Of P-Si/C70 heterojunction diode - Yakuphanoğlu, Fahrettin (Elsevier Science Bv, 2007)
Electronic and photovoltaic properties of p-Si/C-70 heterojunction diode have been investigated. The ideality factor n and barrier height Ob values of the diode were found to be 1.86 and 0.69 eV, respectively. The diode indicates a non-ideal current-voltage behaviour due to the ideality factor being higher than unity. This behaviour results from the effect of series resistance and the presence of an interfacial layer. The series resistance R-s and ideality factor n values were determined using Cheng's method and the obtained values are 2.21 X 10(5) ohm and 1.86, respectively. The device shows photovoltaic behaviour with a maximum open-circuit voltage of 0.22 V and a short-circuit current of 0.35 mu A under 6 mW/crn(2) light intensity. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: heterojunction diode; organic semiconductor; Fullerene-C-70